Life after death : the evidence - D'Souza, Dinesh, 1961- (Washington, D.C. : Regnery Pub. ; New York : Distributed to the trade by Perseus Distribution, 2009)
Drawing on some of the most powerful theories and trends in physics, biology, philosophy, and psychology, D'Souza concludes that belief in life after death offers depth and significance to this life.
Let's stop pretending : the big question considered in a new way -- Vendors of unbelief : atheist false advertising -- A universal longing : two types of immortality -- View from the edge : exploring near-death experiences -- The physics of immortality : multiple universes and unseen realms -- Undeniable teleology : the plot of evolution -- The spiritual brain : finding the soul within the body -- The immaterial self : how consciousness can survive death -- Out of this world : philosophy discovers the afterlife -- The impartial spectator : eternity and cosmic justice -- Good for society : the transcendent roots of secular values -- Good for you : the practical benefits of belief -- Life everlasting : eternity right now.
Includes bibliographical references (p. 239-257) and index.
Keywords: Future life -- Christianity; Immortality; Near-death experiences; Future life -- Christianity; Immortality; Near-death experiences